No más, nada más. Formation of Adverbs of Exclusion (‘only’) - Herrero Ruiz de Loizaga, Francisco Javier (2020)
We study in this paper the development of the adverbial value ‘only’ of no más y nada más. We start from the data provided by the corpora of the Real Academia and we take also into account the Davies’ Corpus del Español (CE) and PRESEEA. The appearance of no más with the value of ‘only’ occurs from the first Castilian texts, probably due to a reduction in the sequence y no más postponed to the element on which it focuses. This construction, grammaticalized into a focus marker, is frequent in medieval Spanish and in the Golden  Age. Since the 18th century, nada más is documented with the value ‘solamente’, and its use grows in European Spanish, while no más falls in disuse. Instead, the form no más remained throughout Latin America, where it develops new values.